(untitled) (Research, Society and Development, 2021)
Objective: To describe the construction and validation of an educational podcast in health with active participation of nursing academics. Method: Methodological study developed in two stages. In the first stage an educational podcast was built with nursing academics. Using the genre radiophonic piece to promote health in leprosy. In the second, the podcast was submitted to content validation by 22 multidisciplinary experts from the areas of health, communication, education and educational technology. The data were analyzed in the software SPSS® Statistics, version 20.0, and the I-IVC Content Validity Index was calculated. Results: IVC was above 0.80 and concordance was satisfactory in most items. Regarding relevance, 25 of 30 items had I-IVC above 0.80 among judges, considering it adequate for use in health education actions. The five items below 0.80 have been changed as suggested. Conclusion: Building and validating the educational podcast in a participatory manner allowed the students to know an educational tool in audio format, and the radio piece as a playful way of carrying educational contents, allowing to visualize that it is possible to elaborate and disseminate educational contents based on the dialogicity, in which the various actors involved are protagonists in the production and diffusion of contents.